The Vienna Genesis Material analysis and conservation of a Late Antique illuminated manuscript on purple parchment - Hofmann, Christa (Böhlau, 2020)
The Vienna Genesis (Austrian National Library, Codex Theologicus graecus 31) is a fragmentary Greek manuscript of the Book of Genesis written on purple dyed parchment with silver ink. It is assumed that the book was created in the first half of the 6th century in the Near East. 24 folios with 48 miniatures have survived and have been stored at the Austrian National Library since 1664. The Vienna Genesis is famous for its rich cycle of biblical illuminations. The silver ink's degradation, which has resulted in extensive damage to the parchment, was already observed in the 17th century. In a three-year research project the parchment, the silver inks, the pigments and dyes were investigated. The detailed material analysis formed the base for conservation and preservation of the manuscript. The book describes the different studies of the project and their results: How was parchment made in Late Antiquity? How was parchment dyed purple? What is the purple dye of the Vienna Genesis? What is the composition of the silver ink and what are the causes of the severe damage? Which pigments were used by the different painters? How can the Vienna Genesis be best conserved for the future?
Description based on print version record.
KU Open Services
Keywords: Art / History; Arts; Electronic books